PEMBENTUKAN SELF CONTROL SISWA MELALUI MATA PELAJARAN AQIDAH AKHLAK (Studi Kasus Kelas XI MA Bahrul Ulum Besuk) - M. Thufail Muttaqin (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2020)
The importance of an educator through education to be able to form student self-control is an effort to overcome all adolescent problems that occur at school age, especially at MA Bahrul Ulum. Therefore, the authors are interested in conducting research with the title Formation of Student Self Control through Aqidah Akhlak Subjects (Case Study of MA Bahrul Ulum Besuk Probolinggo)